The The effect of soaking coconut fiber in an alkaline solution on the tensile strength of composites - Arisetya, Danny Arisetya Saputra; Widodo, Akhmad Basuki; Azhar, Ali; Baroroh, Intan; Kristiyono , Tri Agung (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
Over time, the world's composite materials industry is increasingly developing. Generally, fiberglass-reinforced composite materials are developed. However, fiberglass fibers are expensive and not environtmentally friendly. The aim of this research was to determine the effect of composites reinforced with coconut fibers soaked in alkali. Specimen making using coconut fiber reinforcement that is pre-soaked using an alkaline chemical compound (Na) with a concentration of 5%. This study carried out tensile testing with variations of coconut fiber and soaked it in alkaline chemical compounds for 1-4 days. The measurement of the tensile strength value in the composite refers to the ASTM D638-02 standard and the tensile strength value will be analyzed using the ANOVA method to determine the significant effect on the soaking treatment of NaOH. The results of the tensile strength test in this study are far from the standard results that have been set by the Indonesian Classification Bureau (BKI) in 2021. So, coconut fiber with alkaline soaking for 1-4 days cannot be used as a substitute for fiberglass as a composite material reinforcement to be applied as the main material of the ship.